2020
DOI: 10.1088/1755-1315/440/5/052033
|View full text |Cite
|
Sign up to set email alerts
|

The Ventilation Improvement Assessment of Sky Gardens-A Case Study of Hysan Place

Abstract: With the modernization and urbanization in recent decades, a mounting number of buildings has been built. Due to the limited land, these buildings were built higher and higher and side by side which created ‘Wall Effect’ blocking the wind and reducing air ventilation. It eventually led to bad thermal comfort of people. Therefore, sky gardens are increasingly important today, as they can significantly contribute to improving air ventilation by reducing ‘Wall Effect’. In order to know better about the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Supporting research with applications is very important to put in practice the preliminary results obtained from this simulation study and to verify the potential therapeutic effects of the healing garden proposal on users. But simulation studies is used to accurately and vividly represent the spatial position relationship between solids (Barnhart et al, 1998;Bitter and Corral, 2014;Kerr and Lawson, 2020;Liu and Huang, 2020;Lotfi et al, 2020;Pasini et al, 2014;Piga, 2017;Purcell et al, 1994;Purcell and Lamb, 1984;Sakıcı, 2009;Suresh et al, 2011;Torbati, 2018;Zhao, 2021) . In addition to study limitations, the sample in the experimental design was limited due to participant availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting research with applications is very important to put in practice the preliminary results obtained from this simulation study and to verify the potential therapeutic effects of the healing garden proposal on users. But simulation studies is used to accurately and vividly represent the spatial position relationship between solids (Barnhart et al, 1998;Bitter and Corral, 2014;Kerr and Lawson, 2020;Liu and Huang, 2020;Lotfi et al, 2020;Pasini et al, 2014;Piga, 2017;Purcell et al, 1994;Purcell and Lamb, 1984;Sakıcı, 2009;Suresh et al, 2011;Torbati, 2018;Zhao, 2021) . In addition to study limitations, the sample in the experimental design was limited due to participant availability.…”
Section: Discussionmentioning
confidence: 99%
“…Applying virtual reality technology to landscape design helps speed up the design process (Bai, 2020). Many studies reveal that simulation studies can be used to determine the visual effect of the area and positive effect on user (Akçayır and Akçayır, 2017;Barnhart et al, 1998;Bitter and Corral, 2014;Bower et al, 2014;Kerr and Lawson, 2020;Lotfi et al, 2020;Liu and Huang, 2020;Pasini et al, 2014;Piga, 2017;Purcell et al, 1994;Purcell and Lamb, 1984;Sakıcı, 2009;Suresh et al, 2011;Torbati, 2018;Uzunboylu and Yıldız, 2016;Zhao, 2021). The proposed design included activities like resting, walking, observation, sitting, circulation, discovery walks, socialization, exercise and feeling spaces and offered users the choice of activities in sunny or shaded areas (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…生活态度的舞台 [62,64] 。意大利、西班牙等国家 举行的"阳台派对""阳台音乐"等社交活 动,以新兴社交媒体的形式促进了集体赋权, 成为疫情期间缓解消极情绪、减小隔离心理 成本的有效手段 [65] 。中韩两国学者分别开展了 "Garden on the Balcony"(GOB)与"Iplant" 之一。不良的建筑通风和各种挥发性污染源 是产生病态建筑综合征的主要原因 [67][68][69] 。开放 式阳台可以作为集风斗,将空气吸入建筑物, 作为过渡空间控制和诱导室外气流进入室内, 增加自然空气流动,通过对气流的疏导循环 带动热量的转移 [70][71][72][73] ,发挥重要的"呼吸作 用" [12] 。Xue等 [74] 的一项问卷调查研究表明, 带玻璃或铁艺栏杆的开放式阳台能够减少眩 光和过热问题,间接影响居民的热舒适度; Bhikhoo等 [75] 进行的一项模拟实验显示,拆除 阳台后住宅内部的过热天数相对于拆除前增 加了19.94%;Izadyar等 [76] 研究发现,较小的 阳台开门尺度可产生更好的热舒适性,而较 小的深度尺寸(<2 m)会导致相邻客厅的平 48,57,77] 。具有亲自然性和 美感的阳台环境能够提升热舒适度 [78] ,配置阳 台绿化的室内空间可以降低噪声 [79] 、保持温 度 [80] 、减少温室气体排放 [81] 、维持碳氧平衡 [82] 。 阳台绿化可以有效净化空气,吸收粉尘和二 氧化碳,降低空气中PM 2.5 的浓度,以及吸咐 室内家具、装饰装修过程中释放的有害物质, 减少呼吸道疾病、哮喘和肺癌的发病概率 [83][84][85][86] 。 陈秋瑜等 [87] 通过实测与实验相结合的方法证 明了植物活墙在消除空气污染物和总挥发性 有机化合物方面的作用;王珂 [88] 通过封闭测…”
Section: -6月新冠病毒疫情暴发期间,阳台成为人unclassified
“…Notwithstanding, it is evident that most studies concerning people's satisfaction with health promotion in sky gardens are usually conducted in more advanced countries, especially Singapore [8,16,17]. Again, such studies have extensively reported the environmental, social, urban, architectural, and economic benefits of large-scale, urban-iconic sky gardens, such as rooftop gardens and podium gardens [4,5,8,10,[17][18][19][20][21]. To a certain extent, the small-scale and other functions of sky gardens scattered in high-rise buildings, such as sky courtyards, sky terraces, and skybridges, have been neglected.…”
Section: Introduction 1background Of the Studymentioning
confidence: 99%